Mudim Sdn Bhd / Alif Asyraf Azmi - Azmi, Alif Asyraf (2022)
Perniagaan Mudim Zakaria (MUDIM) as one of the small and medium Enterprises (SME) in Malaysia that manufacture food products. MUDIM was established since 1987 in Kedah. After 30 years of operations mudim will continue to produce high quality of products that meet customer demand within Malaysia and foreign. In march 2019, perniagaan mudim zakaria has been changed to mudim zakaria food industries sdn bhd. Main activities mudim are a manufacturer of sweet soy sauce, chili sauce and vinegar. Mudim also do promotes and distributes the company's product to the local market. In yearly 2005, MUDIM has started to market its products throughout Malaysia, which previously only included Kedah, Perlis and Penang.